A qualitative evaluation of voucher payment system in JKMM, Seri Negeri / Nur Amanina Abd Rahman - Abd Rahman, Nur Amanina (2011)
This case study was conducted to investigate the problems or issue that occurs while processing the payment vouchers in finance unit, JKMM Seri Negeri. The main focus of this study is to explore the performance of finance unit in term of their performance in processing the payment vouchers. This unit faced a few problems during processing the voucher payment. So, the corrective action will be taken to solve the problems. Besides that, the researcher also gives a few recommendations to resolve or reduce the problem that is faced by finance staff. To assess and evaluate the needed information about the problems, staffs in financial units in JKMM who responsible to process the payment voucher was chosen. Data for the research was collected through interviews, observation and internet resources. The issues in finance unit arise when supporting documents to approve payment vouchers were not always complete, or most of the payment delayed because of technical problems such as due to system down, system crisis, inefficient SPEKS system and also due to the pressure imposed by the administration at the end of the year. All this problem occur while processing the payment voucher because of every section / unit in JKMM do not expose with the proper procedure of applying payment claim and also because of the inefficient and the weaknesses of SPEKS system which is system used to process the payment voucher.